2001
DOI: 10.1179/016164101101198758
|View full text |Cite
|
Sign up to set email alerts
|

Physiological levels ofβ-amyloid induce cerebral vessel dysfunction and reduce endothelial nitric oxide production

Abstract: beta-amyloid (A beta), the major component of senile plaques in Alzheimer's disease (AD), normally circulates in the blood at nanomolar levels but is elevated in AD. Previous studies have found that high concentrations (10(-5)-10(-4) M) of A beta result in neuronal cell death. Here we show that physiological levels of soluble A beta can induce dysfunction in perfused rat cerebral vessels and in cultured endothelial cells. At concentrations of 10(-9)-10(-6) M, A beta induced a significant concentration-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…Similar activities have been reported for Ab, which inhibits cerebral blood flow, counteracts acetylcholine activity on blood vessels, inhibits angiogenesis and is cytotoxic for endothelial cells. 51,52 The effect of Ab on cell surface-associated ATP synthase complex in endothelial cells may account for the cerebral amyloid angiopathy aspect of Alzheimer's disease pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Similar activities have been reported for Ab, which inhibits cerebral blood flow, counteracts acetylcholine activity on blood vessels, inhibits angiogenesis and is cytotoxic for endothelial cells. 51,52 The effect of Ab on cell surface-associated ATP synthase complex in endothelial cells may account for the cerebral amyloid angiopathy aspect of Alzheimer's disease pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo studies with isolated cerebral arterioles show that synthetic Aβ 40 (and to a lesser degree Aβ 42 ) induces direct vessel constriction, enhanced response to vasoconstrictors, and reduced response to vasodilators (14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…These alterations could depend on the damaging effect of circulating Ap and ROS. The Ap peptide, generated from the amyloid p precursor protein (APP), is capable of interacting with endothelial cells to produce superoxide radicals, and inhibits NO generation or action (10,12). The endothelium also represents a major target of oxidative stress, which plays a relevant role in the pathophysiology of several vascular disorders (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Ap may damage the vascular endothelium. In particular, it has previously been suggested that a slight increase in Ap above its physiological levels in the circulation, as found in the early stages of AD, can induce a decrease in NO production that may lead to vasoconstriction and ischemia, while high concentrations ofAp stimulate endothelial cell death (12).…”
mentioning
confidence: 99%